High HIV Prevalence Associated with Unsafe Injection Practices among Male Injecting Drug Users in Chennai City, Tamil Nadu State, India - Chandra Pauline Dinakar; Roshanara Begum; Gifty Immanuel (Social Medicine Publication Group, 2011)
Substance abuse is a skyrocketting problem in India today.The intertwined epidemics of HIV/AIDS and injecting drug use are among the most emerging public health problems in India .Intravenous Drug Usage (IVDU) was found to be more prevalent among the ex-prisoners who were visiting the World Vision of India. The objective of this study was to determine the prevalence and correlates of HIV infection among a sub-sample of frequently incarcerated community-based injecting drug users (IDUs) in Chennai city, India. 180 injecting drug users were recruited and interviewed using a structured questionnaire regarding their socio-demographics and HIV risk characteristics. Datas were analyzed using χ2 and multiple logistic regression to estimate odds ratios (OR) and 95% confidence intervals (CI). The prevalence of HIV infection was 69.4% among male injecting drug users. In the multivariable analysis, a history of shared drug injection inside prison (OR, 2.45; 95% CI, 1.01-4.3) and that of multiple incarcerations (OR, 4.15; 95%CI, 1.08-8.03); and tattooing (OR, 2.9; 95% CI, 1.80 -3.78) were associated with significantly higher prevalence of HIV infection. This study proved that incarceration-related exposures and tattooing proved to be the main correlates of HIV-1 infection. Urgent and comprehensive HIV prevention programs and cost effective rehabilitation centers for injecting drug users in and out of prison are of prime importance to prevent further transmission of HIV infection.